TRIM29 inhibits miR-873-5P biogenesis via CYTOR to upregulate fibronectin 1 and promotes invasion of papillary thyroid cancer cells - Wu, Tong (Cell Death Dis, 2020)
Papillary thyroid cancer (PTC) is the most common endocrine tumor with an increasing incidence, has a strong propensity for neck lymph node metastasis. Limited treatment options are available for patients with advanced or recurrent metastatic disease, resulting in a poor prognosis. Tripartite motif protein 29 (TRIM29) is dysregulated in various cancer and functions as oncogene or tumor suppressor in discrete cancers. In this study, we found that both TRIM29 and fibronectin 1 (FN1) were upregulated with positive correlation in PTC tissues. Neither overexpression nor downregulation of TRIM29 altered the proliferation of PTC cells significantly. Overexpression of TRIM29 significantly promotes, while knockdown of TRIM29 significantly decreases migration and invasion by regulating FN1 expression in PTC cells. In terms of mechanism, we found that TRIM29 altered the stability of FN1 mRNA via regulation of miR-873-5p expression. The current study also demonstrated that long non-coding RNA (LncRNA) CYTOR suppressed maturation of miR-873-5p via interaction with premiR-873, and TRIM29 decreased miR-873-5p via upregulation of CYTOR. This study suggests that involvement of TRIM29 in migration and invasion in PTC cells may reveal potential metastatic mechanism of PTC and represent a novel therapeutic target and strategy.